PENGARUH IHSG, NILAI TUKAR, DAN BI RATE TERHADAP KINERJA REKSA DANA PENDAPATAN TETAP (Studi Pada Reksa Dana Pendapatan Tetap Yang Terdaftar Di Otoritas Jasa Keuangan Periode Tahun 2015 – 2019) - Andhika Septiaji (Jurnal Ilmiah Mahasiswa FEB, 2020)
Abstract: This study aims to determine the effect of the IDX Composite, Exchange Rate and BI Rate on fixed income mutual funds. This research was conducted using the Treynor method to calculate the performance of a fixed income mutual fund. The type of research used in this research is explanatory research with a data collection period of 5 years from 2015 2019. The population in this study were all active fixed income mutual funds registered with the Financial Services Authority during the period 2015 - 2019. The sample selection technique used was purposive sampling method so that there were 8 fixed income mutual fund products. The type of data used is secondary data taken from the web pages of the Indonesia Stock Exchange, Financial Services Authority, Bank Indonesia and Bareksa. The results of this study indicate that the IDX Composite, Exchange Rate and BI Rate variables have a significant effect on the performance of fixed income mutual funds.Keywords: IDX Composite, Exchange Rate, BI Rate, Mutual Fund Performance, Fixed Income Mutual Funds